A case of bilateral renal oncocytomas in the setting of Birt-Hogg-Dube syndrome - Brian Covello, MD; Sean Kaufman, MD; Elizabeth Whittington, MD; Orlando Enrizo, MD (Radiology Case Reports, 2021)
Birt-Hogg-Dube syndrome is a rare autosomal dominant disorder characterized by pulmonary cysts, renal tumors, and dermal lesions. This syndrome results from a mutation in the gene folliculin, located on chromosome 17p11.2. Herein, a case is described in which the presence of bilateral renal oncocytomas led to the diagnosis of Birt-Hogg-Dube syndrome via an interdisciplinary effort by radiology, pathology, and primary care medicine. No radiographic features alone are sufficient to confirm the diagnosis of Birt-Hogg-Dube. A high index of suspicion must be maintained by both the pathologist and radiologist in the appropriate clinical setting.